Gender Differences in Competitiveness: The Role of Social Incentives - Michalis Drouvelis; Mary L. Rigdon (Center for Economic Studies and ifo Institute (CESifo), 2022)
The provision of social incentives in the workplace, where performance benefits a charitable cause, has been frequently used in modern organizations. In this paper, we quantify the impact of social incentives on performance under two incentive schemes: piece rate and a winner-take-all tournament. We introduce social incentives by informing individuals that 50% of their performance earnings will be donated to a charity of their own choice. Our findings indicate that, in the presence of social incentives, women increase their performance by approximately 23% and 27% in the piece rate and tournament payment schemes, respectively. These effects are sizable and significant. Despite the fact that women also become more confident when social incentives are used, their willingness to compete is not affected due to their general lack of willingness to take financial risks.
Keywords: C92; D64; J16; J20; 330; social incentives; task performance; piece rate; tournament; competitiveness; gender differences